The Productive Waqf Land Utilization Agreements in Indonesia: Legal Status and Financial Scheme - Nurjamil Nurjamil; Tajul Arifin; Hasan Bisri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research was conducted to determine the legal status, funding schemes and benefit sharing of the active waqf land use agreement in Indonesia. This research adopts a normative juridical approach, examining the legal dimensions of the subject matter based on statutory norms, particularly those related to waqf. It also employs an analytical descriptive method, whereby the collected data is analyzed to provide a comprehensive depiction of the utilization of productive waqf land in Indonesia. Data collection was conducted through literature review and in-depth interviews with commissioners of the Indonesian Waqf Board and practitioners in the Islamic financial services sector. The findings were then analyzed using qualitative data analysis techniques. The agreement on the use of beneficial waqf land in Indonesia is in accordance with both Islamic law and positive law. In large-scale ventures, investors can include financial institutions in the Sharia Non-Bank Financial Industry, such as sharia venture capital with mudarabah or musyarakah, or cooperate with sharia financial technology company via a crowd-funding agreement. This study is particularly valuable for waqf managers and scholars, as it can aid in developing contract-based utilization arrangements and financing schemes grounded in financing rules. Furthermore, the study highlights the potential of sharia venture capital and sharia financial technology as promising funding schemes for waqf-based ventures, offering innovative solutions for the sustainable growth of waqf land utilization.